Facial nerve paralysis in nasopharyngeal carcinoma: a case report - Jarod Wahyu Kristiyanto; Muyassaroh Muyassaroh; Dwi Antono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Nasopharyngeal carcinoma (NPC) is cancer originating from the mucosal lining of nasopharynx, with the highest predilection in the fossa of Rosenmüller. One-fifth of NPC cases have cranial nerve complications. The location of Rosenmüller's fossa which is adjacent to foramen lacerum and middle base of the cranium allows the tumor to extend directly into the cranium and surrounding cranial nerves. This paper reported a case of facial nerve paralysis in NPC. A 55-year-old man came to the Ear-Nose-Throat (ENT) Clinic at Dr. Kariadi General Hospital, Semarang with complaints of facial pain on the right side, headache, a lump on the left neck, fullness in ears, and nosebleed. However, the patient did not complain of double vision. After a thorough history taking, physical examination, radiology, and histopathology tests, the patient was diagnosed with WHO 3 ECOG I T3N2M0 stage III NPC with House Brackmann III facial nerve paresis at the level of Mastoid segment. The patient was treated using chemotherapy treatment by an ENT specialist with a chemotherapy regimen of paclitaxel-cisplatin for 6 cycles. In conclusion, although rare, NPC can cause facial nerve paralysis.